EFEKTIVITAS PENGGUNAAN MODIFIKASI LAMPU LED SEBAGAI ALAT BANTU PENANGKAPAN PANCING HAND LINE DI PERAIRAN TANAH BERU SULOERE KABUPATEN BULUKUMBA - Rahmat Bin Aburaera; Nunung Hasrianti (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2025)
The objectives of this study are: 1) Analyzing the composition of the types of suloere catches on hand line fishing in the waters of Tanah Beru, Bulukumba Regency. 2) Analyze the distribution of the dominant fish size caught by suloere on hand lines in the waters of Tanah Beru, Bulukumba Regency. 3) Analyzing the effectiveness of red, yellow and blue LED (Light Emitting Diode) lights on hand lines made from bottle waste in the waters of Tanah Beru, Bulukumba Regency. This research was carried out from May to June 2023 in the waters of Tanah Beru, Bontobahari District, Bulukumba Regency. In this study, the experiment to be carried out is the use of LED suloere lights as a catching aid. 1) The suloere catch in long fishing rods is yellow scallops (Selaroides leptolepis), kite (Decapterus sp.), red snapper (Lutjanus malabaricus), kurisi (Nemipterus bathybius.), sea eel (Gymnothorax sp.) and cockatoos (Scarus guacamaia). 2) The highest distribution of size and weight of catch was obtained by flying fish with a length distribution of 121-154 mm with a weight of 19-68 grams caught on a blue LED suloere. 3) Comparison of the capture results using red, yellow, and blue LED suloere capture aids showed real different results